The Determinant of CSR Disclosure of Mining Industry Listed in Indonesia Stock Exchange - Deitiana, Tita (Asian Business Review, 2015)
The purpose of this study to determine and obtain empirical evidence about the influence of firm characteristics on a disclosure of corporate   social   responsibility (CSR) in the annual reports of mining companies listed on the Indonesian Stock Exchange (BEI). Corporate    social   disclosure needs to be done as a form of communicating the social and environmental   impacts of economic activities on the organization of special interest groups; the characteristics   of the company used as the study include profitability, leveraged, growth rate, firm size, market capitalization, media exposure, and ownership.This research is aimed to know the influence of financial performance according to management decision that doing corporate social responsibility to public society, investor and the stock holder. The Determinants of Corporate Social Responsibility have been investigated by scholars and practitioners by employing a variety of methods and factors. The purpose of this research is to test and analyze empirically the influence of profitability, leveraged, growth rate, firm size, market capitalization, media exposure and ownership toward corporate social responsibility disclosure.Sampling Method used in this study is the method of purposive sampling is the sampling method based on certain criteria. The Sample in this research mining companies that are listed at Indonesia Stock Exchange over six years period 2016 until 2012. This research used purposive sampling method. Only 16 companies met the criteria and taken as a sample. The Analyst used was multiple regression analysis, which is proceeded by a test consisting of the assumption of classical test for normality, heteroscedasticity test, a test of multicollinearity and autocorrelation. Hypothesis testing is F test and t test.The empirical evidence from this study show that firm size and board of commissioner have influence toward corporate social responsibility disclosure.While profitability,public share holder (ownership), growth rate, media exposure and leveraged  do not have influence toward corporate social responsibility disclousure. Overall, the independent variables influence debt policy simultaneously.JEL Classification Code: G28